Electrochemical reforming of methane using SrZr0.5Ce0.4Y0.1O3-δ proton-conductor cell combined with paper-structured catalyst. (7th February 2020) - Maeda, Shota; Shiratori, Yusuke; Kurashina, Daisuke; Fujisaki, Takaya; Leonard, Kwati; Matsumoto, Hiroshige
Abstract: Reforming of hydrocarbon which is an important hydrogen production method proceeds in two steps, i.e. steam reforming and shift reaction. Due to different thermodynamics, the two reactions are conventionally conducted at different temperatures. This study examines one step methane reforming by use of proton-conducting electrochemical cell in combination with a reforming catalyst. Promotion of the reforming reaction was intended by extracting hydrogen via electrochemical hydrogen pumping with a proton conductor cell. In order to compensate for the slow kinetics of the steam reforming, a paper catalyst loaded with Ni was placed in front of the electrochemical cell. Electrolyte support cells were used to verify this concept, and the effect of the electrochemical hydrogen pump was investigated from the composition of the outlet gas. Electrode support cells using a thin film electrolyte was used to reduce overvoltage. It is demonstrated that the steam reforming reaction and the shift reaction take place in one electrochemical cell. Effective catalyst placement and energy efficiency is discussed. Graphical abstract: Reforming of methane was performed for hydrogen producing with proton conducting SrZr0.5 Ce0.4 Y0.1 O3-δ (SZCY541) and Ni-loaded paper-structured catalyst (Ni-PSC). When Ni-PSC is used as anode, electrode-supported cell shows enough H2 evolution rate in agreeing with Faraday's law. Image 1 Highlights: Methane reforming was examined using protonic SrZr0.5Ce0.4Y0.1O3-δ electrolyte. Ni-loaded paper-structured catalyst effectively improved the conversion of CH4 to H2 . Electrode-support cell was more effective for steam reforming and the shift reaction.